Can Radiologist Training and Testing Ensure High Performance in CT Colonography? Lessons From the National CT Colonography Trial - Fletcher, Joel G. (2010)
OBJECTIVE: The objective of this article is to describe the experience of the National CT Colonography Trial with radiologist training and qualification testing at CT colonography (CTC) and to correlate this experience with subsequent performance in a prospective screening study. SUBJECTS AND METHODS: Ten inexperienced radiologists participated in a 1-day educational course, during which partial CTC examinations of 27 cases with neoplasia and full CTC examinations of 15 cases were reviewed using primary 2D and 3D search. Subsequently 15 radiologists took a qualification examination composed of 20 CTC cases. Radiologists who did not pass the first qualification examination attended a second day of focused retraining of 30 cases, which was followed by a second qualification examination. The results of the initial and subsequent qualification tests were compared with reader performance in a large prospective screening trial. RESULTS: All radiologists took and passed the qualification examinations. Seven radiologists passed the qualification examination the first time it was offered, and eight radiologists passed after focused retraining. Significantly better sensitivities were obtained on the second versus the first examination for the retrained radiologists (difference = 16%, p < 0.001). There was no significant difference in sensitivities between the groups who passed the qualification examination the first time versus those who passed the second time in the prospective study (88% vs 92%, respectively; p = 0.612). In the prospective study, the odds of correctly identifying diseased cases increased by 1.5 fold for every 50-case increase in reader experience or formal training (p < 0.025). CONCLUSION: A significant difference in performance was observed among radiologists before formalized training, but testing and focused retraining improved radiologist performance, resulting in an overall high sensitivity across radiologists in a subsequent, prospective screening study.